Les possibilités de la connaissance humaine. La perspective cartésienne - Drozdowicz, Zbigniew (Wydawnictwo Fundacji Humaniora, 2014)
The cognitive perspective presented by Descartes involves both cognitive minima and maxima. They are based on a common assumption that knowledge is only that which is absolutely certain and absolutely true. They differ in terms of the threshold which needs to be crossed in order to gain not only certain and true but also complete knowledge. Cognitive minima and maxima are presented in the works of this philosopher in many different ways since each work has its own aim. In the ‘Rules for the Direction of the Mind,’ the aim is to point out the infallible criteria of certainty and truth. In the ‘Discourse on the Method,’ the aim is to determine infallible methodic and methodological rules which make it possible to attain certainty and truth. The aim of the ‘Meditations on First Philosophy’ is, first, to point out the so called Archimedean point of infallible cognition and knowledge, and second, to achieve such consciousness and self-consciousness as to cross the threshold between res cogitans (thinking substance) and res extensa (extended thing). All other things belong either to the first or to the second world. To point it out constitutes the Cartesian cognitive maximum.
Keywords: human cognition; cognitive minima; cognitive maxima; Cartesian ideal